Konsep Rahmatan Lil ‘Alamin pada QS. Al-Anbiya: 107 (Kajian Tafsir Qur’an) - Fitrah Dinanti Massofia; Rahmawati (Jurnal test, 2023)
Islam religion embraces in all aspects of natural life and everything in it, even to the end of the day. This study contain interpretation of QS Al-Anbiya: 107 according to various interpretations from scholars. so that the meaning of Islam rahmatan lil 'alamin is often assumed as special feature that distinguishes it from other religions. This study aims to find out the meaning of the interpretation of Rahmatan lil 'Aalamiin contained in QS. Al-Anbiya: 107. As well as to discuss how concept of Islam in the view of commentators. This research use library research whose activities are carried out by analyzing literature from textbooks. The method used in data collection from Miles and Huberman consists of data collection, data reduction, data presentation, and drawing conclusions. Analyze the data with descriptive qualitative which shows the results of study that: 1) Rahmatan lil'alamin is a mercy given to all creatures so that humans must respect one another to be able to achieve prosperity in life. 2) Islam is religion of rahmatan lil'alamin, meaning that Islam is the last religion revealed by Allah of the universe to manage the entire universe with grace and compassion. So that the grace obtained by the Prophet Muhammad SAW has an impact on his people.